Consideration of Petitions for Pardon in the Russian Federation: Novelties of 2020 - VYACHESLAV I. SELIVERSTOV (Пенитенциарная наука, 2021)
Introduction: the paper analyzes the amendments made by the Decree of the President of the Russian Federation no. 797 of December 14, 2020 to the Decree of the President of the Russian Federation of December 28, 2001 no. 1500 “On commissions for pardon in the territories of constituent entities of the Russian Federation” and the norms of the new Regulation on the procedure for considering petitions for pardon in the Russian Federation. Methods: comparative legal method and method of interpretation of legal norms. Results: having analyzed legal documentation on the activities of the commissions and having considered convicts’ petitions for pardon, we point out the following positive changes: an increase in the rotation period of members of the commissions for pardon; clarification of their analytical and control functions; inclusion of social adaptation in the number of circumstances taken into account when considering the issue of pardon; exclusion of personal data of individuals recommended for pardon by the highest official of a constituent entity of the Russian Federation from publication in the mass media; taking into account the opinions of the victims of the crime. We think that negative changes are those that have created new problems in the form of contradictions with the norms of criminal and penal legislation. These include the possibility of granting pardon to persons serving other criminal law measures, and applying for pardon directly to the commission on pardons, bypassing the administration of institutions and bodies that execute sentences. Conclusion: the current task to expand the practice of granting pardon cannot be solved by adopting a new Regulation on the procedure for considering petitions for pardon in the Russian Federation.